Impact of compulsory participation of medical students in a multiuser online game to learn radiological anatomy and radiological signs within the virtual world Second Life - Rudolphi Solero, Teodoro; Lorenzo Álvarez, Rocío; Ruiz-Gómez, Miguel José; Sendra-Portero, Francisco (Wiley, 2021)
Competitive game- based learning within Second Life enables effective teaching of basic radiological anatomy and radiological signs to medical students, with good ac-ceptance and results when students participate voluntarily, but unknown in a com-pulsory context. The objectives of this study were to reproduce a competitive online game based on self- guided presentations and multiple-choice tests in a mandatory format, to evaluate its development and student perceptions compared to a volun-tary edition in 2015 (N= 90). In 2016 and 2017, respectively, 191 and 182 third-year medical students participated in the game as a mandatory course activity. The mean (±SD) score of the game was 74.7% (±19.5%) in 2015, 71.2% (±21.5%) in 2016, and 67.5% (±21.5%) in 2017 (P< 0.01). Participants valued positively the organization and educational contents but found the virtual world less attractive and the game less interesting than in the voluntary edition. The experience globally was rated with 8.2 (±1.5), 7.8 (±1.5), and 7.1 (±1.7) mean points (±SD) in a ten- point scale, in the 2015, 2016, and 2017 editions, respectively (P< 0.05). Competitive learning games within virtual worlds like Second Life have great learning potential in radiology, but the mean score in the game decreased, acceptance of virtual world technology was lower, and opinion about the game was worse with a compulsory participation, and even worse when dropouts were not allowed. Under the conditions in which this study was con-ducted, learning games in three-dimensional virtual environments should be volun-tary to maintain adequate motivation and engagement of medical students.
Keywords: Educación - Investigación; Education research; E-learning/computers; Game-based learning; Gross anatomy education; Radiology education; Medical education; Undergraduate education; Virtual worlds